Peranan Akuntansi Pertanggungjawban Dalam Penilaian Kinerja Pusat Biaya - Meri Ananda Martianti; Iriyadi Iriyadi (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
Basically every company has a future plan. However to design the plan a study of the results from the previous year was needed. Accountability accounting is a financial reporting system that is related to the budget and realization, this is to appoint the competent in an organization. The purpose of this study was to find out how the role of accountability accounting in the performance assessment of cost centers in PDAM Tirta Pakuan Kota Bogor. The Method used is descriptive and qualitative analysis. The data used to measure performance is the 2016 financial report. The result of the study show that accountability accounting plays an important role because of the annual monthly and annual performance appraisal and the basis for budgeting that has been implemented by the PDAM Tirta Pakuan Kota Bogor. The result of performance appraisal are used to evaluate financial statements made by managers in optimizing costs, income, investment and profits in the company. Keywords: Accountability accounting, cost center performance.